2008
DOI: 10.1007/s00109-008-0373-8
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-kappa B signaling in skeletal muscle atrophy

Abstract: Skeletal muscle atrophy/wasting is a serious complication of a wide range of diseases and conditions such as aging, disuse, AIDS, chronic obstructive pulmonary disease, space travel, muscular dystrophy, chronic heart failure, sepsis, and cancer. Emerging evidence suggests that nuclear factor-kappa B (NF-κB) is one of most important signaling pathways linked to the loss of skeletal muscle mass in various physiological and pathophysiological conditions. Activation of NF-κB in skeletal muscle leads to degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
482
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 372 publications
(508 citation statements)
references
References 101 publications
(201 reference statements)
18
482
1
7
Order By: Relevance
“…NF-kB activation in the skeletal muscle of COPD patients may be sufficient for the induction of muscle atrophy [82,83]. Conversely, inhibition of NF-kB restores muscle mass in a number of experimental models of atrophy, implying an important role for NF-kB in this process.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-kB activation in the skeletal muscle of COPD patients may be sufficient for the induction of muscle atrophy [82,83]. Conversely, inhibition of NF-kB restores muscle mass in a number of experimental models of atrophy, implying an important role for NF-kB in this process.…”
Section: Mechanismsmentioning
confidence: 99%
“…NF-kB activation is also implicated in mediating systemic inflammation and may be involved in skeletal muscle weakness in COPD patients [82]. NF-kB activation is important in skeletal muscle atrophy and the inhibition of NF-kB may prevent this in animals [83]. NF-kB activation has also been implicated in several of the comorbidities associated with COPD, including cardiovascular disease, lung cancer, osteoporosis and diabetes [208].…”
Section: Pde4 Inhibitorsmentioning
confidence: 99%
“…Interestingly, the gene expression of NFκB at 2 days in the inflammation group was also unexpectedly reduced in our study. A previous study also reported a reduction in this pro-inflammatory factor in muscle disuse due to immobilization 21 , but the significance of this reduction has not been clarified in the literature to date. Regarding these unexpected findings involving myostatin and NFkB expressions, a previous study showed a relationship between myostatin, TNF-α, and NFkB 41 .…”
Section: Muscle Response To Joint Inflammationmentioning
confidence: 90%
“…MAFbx (also known as atrogin-1) and Muscle Ring Finger-1 (MuRF1) [13][14][15][16] . Muscle fiber CSA reduction is also followed by changes in the regulation of genes related to muscle differentiation and growth (MyoD) 17,18 mass regulation (myostatin) 19 and proinflammatory factors, such as p38 Mitogen-Activated Protein Kinase (p38MAPK), Nuclear Factor kappa B-dependent (NFκB), and Tumour Necrosis Factoralpha (TNF-alpha) [20][21][22] . According to a previous study, the carrageenan injection increases TNF-alpha 23 , a cytokine able to increase the gene expression of MuRF1 and atrogin-1 in rat skeletal muscle 20,24,25 through the NFκB 20 and MAPK 25 pathways, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and oxidative stress are associated with skeletal muscle wasting in various disease states including cancer cachexia, muscular dystrophy, AIDS, sepsis, diabetes, chronic obstructive pulmonary disease (COPD), and cystic fibrosis [5][6][7][8][9]. Muscle wasting occurs as a result of a reduction in protein synthesis, an increase in protein degradation, or both [10][11][12].…”
Section: Introductionmentioning
confidence: 99%